A solution to the slow stabilisation of surface pressure sensors based on the Wilhelmy method - Partridge, Matthew; James, Stephen W.; Tatam, Ralph P. (Sciencematters AG, 2017)
Dynamic measurement of surface pressure is of particular interest in the field of Langmuir monolayers, where the change in surface pressure throughout an experiment can provide information on the properties of the monolayer forming material, or on the reaction kinetics of the monolayer’s interaction with other materials. One of the most common methods for the measurement of dynamic surface pressure is the Wilhelmy plate method. This method measures changes in the forces acting upon a thin plate of material at the air-water interface; this measurement is then converted to surface pressure. One version of this method, which uses filter paper plates at the air-water interface, is particularly popular due to their relatively low cost. However, it has been seen that the use of filter paper plates attached to a Wilhelmy balance requires an initial stabilisation period lasting several hours, during which the readings drift from the original baseline. Here the cause of this drift is explored, considering how changes in the weight of the plate over time influence the assumptions on which the surface pressure is derived from the measurements made by the Wilhelmy balance. A simple method for preventing this drift through pre-soaking of the filter paper plates is presented.
Keywords: Monolayers; Wilhelmy; Langmuir; Surface Pressure; Langmuir Blodgett